Blood Biomarkers in Moderate-To-Severe Traumatic Brain Injury: Potential Utility of a Multi-Marker Approach in Characterizing Outcome - Di Battista, Alex P.; Buonora, John E.; Rhind, Shawn G.; Hutchison, Michael G.; Baker, Andrew J.; Rizoli, Sandro B.; Diaz-Arrastia, Ramon; Mueller, Gregory P. (Frontiers in Neurology, 2015)
Background: Blood biomarkers are valuable tools for elucidating the complex cellular and molecular mechanisms underlying traumatic brain injury (TBI) pathophysiology. Profiling distinct classes of biomarkers could aid in the identification and characterization of both initial injury and secondary pathological processes. The purpose of this study was to characterize the prognostic performance, both individually and combined, of a recently developed multimarker panel of circulating biomarkers reflecting specific pathogenic mechanisms including neuroinflammation, oxidative damage and neuroregeneration, in moderate-to-severe TBI patients. Materials and Methods: Peripheral blood samples were drawn from 85 isolated TBI patients (n=60 severe, n=25 moderate) at hospital admission, 6-, 12-, and 24-h post-injury. Mortality and neurological outcome were assessed using the extended Glasgow Outcome Score (GOSE). A multiplex platform was designed on MULTI-SPOT® plates to simultaneously analyze human plasma levels of s100 calcium binding protein (s100B), glial fibrillary acidic protein (GFAP), neuron specific enolase (NSE), brain derived neurotrophic factor (BDNF), monocyte chemoattractant protein (MCP)-1, intercellular adhesion molecule (ICAM)-5, and peroxiredoxin (PRDX)-6. Results: Unfavorable outcome was associated with elevations in s100B, GFAP and MCP-1. Mortality was related to differences in 6 of 7 markers analyzed. Combined admission concentrations of s100B, GFAP and MCP-1 were able to discriminate favorable versus unfavorable outcome (AUC = 0.83), and survival versus death (AUC = 0.87), although not significantly better than s100B alone (AUC = 0.82 and 0.86, respectively). Conclusion: The multimarker panel of TBI-related biomarkers performed well in discriminating between unfavorable and favorable outcomes in the acute period after moderate-to-severe TBI. However, these combined biomarkers did not outperform s100B alone.